Math virtual assistant

About Snapxam Calculators Topics Go Premium
ENGESP
Go!
1
2
3
4
5
6
7
8
9
0
x
y
(◻)
◻/◻
2

e
π
ln
log
lim
d/dx
d/dx
>
<
>=
<=
sin
cos
tan
cot
sec
csc

asin
acos
atan
acot
asec
acsc

sinh
cosh
tanh
coth
sech
csch

asinh
acosh
atanh
acoth
asech
acsch

Solve the equation functionf(x=(-11x+6+-7x^4+6x^5)(9x-7+12x^2+3x^3))

f\left(x\right)=\left(6x^5-7x^4-11x+6\right)\left(3x^3+12x^2+9x-7\right)

Step by step solution

Problem

$f\left(x\right)=\left(6x^5-7x^4-11x+6\right)\left(3x^3+12x^2+9x-7\right)$

Show full step-by-step solution

Answer

$f\left(x=\left(12x^2+3x^3\right)\left(6-11x-7x^4+6x^5\right)-42+77x-7\left(6x^5-7x^4\right)+54x-99x^2+9x\left(6x^5-7x^4\right)\right)$

Struggling with math?

Access detailed step by step solutions to millions of problems, growing every day!

$f\left(x\right)=\left(6x^5-7x^4-11x+6\right)\left(3x^3+12x^2+9x-7\right)$

Main topic:

Polynomials

Used formulas:

0

Time to solve it:

0.52 seconds